Reversible atrioventricular block during transcatheter ventricular septal defect closure – a serial case report - Indrihapsari, Pratiwi; Putri, Valerinna Yogibuana Swastika (Heart Science Journal, 2025)
Background: The transcatheter ventricular septal defect procedure is a sophisticated intervention that carries potential complications, such as complete heart block. We report two cases of patients who experienced total AV block during transcatheter VSD closure and were successfully treated with steroids and atropine. Case Presentation: Perimembranous VSD was found in a 19-year-old military recruit. A baseline 12-lead EKG showed sinus rhythm and no conduction delays. Echocardiography revealed a 6-9 mm perimembranous VSD. Then the VSD was closed with a VSD Occluder No 10-8. ECG monitor and echocardiography showed a complete atrioventricular block during the procedure. Fortunately, 1mg atropine and 125mg methylprednisolone overcame this. Recurrent atrioventricular block and VSD were not found after the procedure. A 33-year-old male patient was diagnosed with a perimembranous VSD during routine screening. Initial 12-lead electrocardiography was unremarkable, while echocardiographic evaluation revealed a 3-5 mm perimembranous VSD. Transcatheter closure was performed using a VSD Occluder device (No. 10-8). Hemodynamic monitoring and echocardiography demonstrated a complete atrioventricular (AV) block intraoperatively. Pharmacological intervention with 1 mg atropine and 125 mg methylprednisolone resolved the conduction disturbance. Despite this transient complication, the procedure continued with successful device deployment. Post-procedural assessment confirmed complete VSD closure with no residual shunt or persistent AV conduction abnormalities. Conclusions: In the context of transcatheter closure of ventricular septal defects, there exists a risk of atrioventricular block, which can be precipitated by mechanical trauma or compression from the delivery system or device. Ensuring the appropriate sizing of the device is pivotal in minimizing this risk. Continuous heart rhythm monitoring is indispensable during both short-term and long-term follow-up periods.